Fostering Critical Thinking Through E-Worksheets: A Project-Based Approach to Fish Waste Processing Education - Perdana, Dheonardo Putra; Hasnunidah, Neni; Fadiawati, Noor; Jalmo, Tri (Darul Yasin Al Sys, 2025)
Despite the importance of critical thinking in science education, junior high schools often lack effective instructional models that engage students with real-world environmental issues. One such issue, fish waste management, remains underutilised as a learning context, despite its relevance to local communities. This study investigates the effectiveness of project-based learning (PjBL) assisted by e-worksheets in fostering students’ critical thinking skills through the topic of fish waste processing. A quasi-experimental design was employed, involving 30 seventh-grade students in Bandar Lampung, Indonesia. Pre- and post-tests were administered to measure five core indicators of critical thinking: problem identification, information sourcing, hypothesis formulation, clarification, and solution generation. The results, analysed using SPSS 25.0, showed significant improvements across all indicators. For instance, accurate problem identification responses increased from 0% to 47%, and logical hypothesis construction improved from 0% to 37%. Students also reported greater engagement with the digital worksheets, which featured multimedia content, simulations, and open-ended questions. The findings indicate that e-worksheet-assisted PjBL is an effective pedagogical strategy for enhancing students’ analytical thinking, environmental literacy, and meaningful learning engagement across science education contexts.